Design Of 5.8 Ghz Quasi-Yagi Patch Antenna - Manan, Hani Aqilah Wahidah Abd (Universiti Sains Malaysia, 2017)
This dissertation discussed the design of 5.8 GHz quasi-Yagi patch antenna for wireless communications. Most of the researches on the quasi-Yagi antenna designs used a dipole as the driver element. There are also studies conducted on different driver shapes of the antenna. This research focused on the use of patches driver in the quasi-Yagi antenna as it is proven to give the antenna a wider bandwidth and a better radiation pattern which are the needs for the wireless communication applications. The proposed antenna design is a quasi-Yagi antenna with slotted microstrip driver operating at a frequency of 5.8 GHz before forming antenna arrays. The etching of slot on the patch driver is to increase the bandwidth of the antenna, aside from applying antenna arrays, which also enhances the radiation pattern of the antenna. Printed Circuit Board (PCB), ROGERS 4003, dielectric material with relative permittivity of 3.38 and thickness of 0.813 mm, is used in this research. CST Microwave Studio is the simulation tool used to model and simulate the antenna design before translating the output results to PCB hardware fabrication. The fabricated antenna is tested using RF equipment to measure the antenna performance parameters and the results are compared to the simulated results. The conventional quasi-Yagi patch antenna, slotted quasi- Yagi patch antenna, and slotted quasi-Yagi patch antenna array resulted in a broad bandwidth and a high gain. The addition of slots and antenna array have enhance the bandwidth of the antenna and achieve a good radiation pattern. The proposed antenna and its array is suitable for SHF band applications and wireless communication system.